Factor determining functional perception on technology-driven product design: a case study on mobile phone for the elderly - Kingkarn Pijukkana; Nopadon Sahachaisaeree (My University, 2010)
Distinctive human attribute such as age, sex, and cultural background posted much of the problems in the understanding of graphic representation. This research attempts to use pictorial icon in cell phone as a case study to reveal the age and cultural bias between age groups. Most of them are able to operate only the basic features. The study thus has an ultimate goal to discover an universally representation of iconic symbol, which would help enhance the learning ability of senior group in particular, and to improve the usage of other technological oriented appliances in general. Study in three features-complexity of iconic, the visual limitation of the aged, and the interpretation of iconic symbols. The first issue deals with the capability to learn new technology and the recollection. Next, deals with graphic icon visible format -simple, detailed and textual which include size and color. The final issue deals with the 2D/3D format, realistic/symbolic, and with/without textual display. The research found that respondents are proved to be equally able to learn complicated level as younger users. With reading glasses, they are able to visualize and understand simple icons as small as 5-10 mm. Complicated as 30 mm. Graphical icons with textual as 10-15 mm. Bright color for simple icon, cooler tone is for complicated ones. 2D is for familiar objects while 3D and realistic for unfamiliar ones. Textual representation could enhance the understanding of representation as well.
Keywords: Icon; Representation; Symbol (formal); Mobile phone; Relevance; Color perception and design